Myasthenia gravis as one of paraneoplastic neurological syndromes associated with small cell lung cancer. Case report - R. Bunevičiūtė; R. Masaitienė; A. Klimašauskienė (Neurologijos seminarai)
Myasthenia gravis associated with extrathymic malignancies is a rarely diagnosed pathology in clinical practice. We report a case of myasthenia gravis-like syndrome associated with small cell lung cancer. A male patient has been diagnosed with 3 different paraneoplastic neurological syndromes: sensorimotor polyneuropathy, limbic encephalitis and myasthenia gravis-like syndrome which was confirmed by positive repetitive nerve stimulation test. The causal association between small cell lung cancer and myasthenia gravis as a paraneoplastic neurological syndrome (PNS) has not been officially confirmed yet. However, there is increasing evidence in the literature, that myasthenia gravis could be one of the PNS phenotypes of non-thymomatous malignancies.